Synthesis of 3-[2-(1H-imidazol-2-yl)alkyl]-2-thioxo-2,3-dihydroquinazolin-4(1H)-one derivatives - O. A. Zavada; O. V. Tkachenko; I. O. Zhuravel (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Abstract